A manual for writers of research papers, theses, and dissertations : Chicago style for students and researchers / Kate L. Turabian ; revised by Wayne C. Booth, Gregory G. Colomb, Joseph M. Williams, and University of Chicago Press editorial staff. (2007)
Summary goes here